2017
DOI: 10.4172/2167-0897.1000264
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Kangaroo Mother Care by Postnatal Mothers who Gave Birth to Preterm and Low Birth Weight Babies in Public Hospitals, Eastern Ethiopia

Abstract: Introduction: Globally, babies born with low birth weight and preterm accounts for 25 million and 15 million respectively. The magnitude of preterm and low birth weight was 29.1% in Ethiopia by 2011. Around 70% neonatal deaths occur in low birth weight and preterm babies. Most studies demonstrated kangaroo mother care to be more effective than incubator care for these neonates but there are limited studies in Ethiopia. Therefore, the main aim of the study was to assess the acceptability, knowledge, attitude an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 11 publications
4
27
0
Order By: Relevance
“…This study showed that 58% mothers have willingness to implement KMC. This finding was similar with other findings [18][19] but it was lower than other studies [11,25]. In our study 47 (54.7%) of respondents would recommend KMC to other mothers with low birth weight infants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study showed that 58% mothers have willingness to implement KMC. This finding was similar with other findings [18][19] but it was lower than other studies [11,25]. In our study 47 (54.7%) of respondents would recommend KMC to other mothers with low birth weight infants.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that the overall knowledge and practice of caretakers on kangaroo mother care were 68.6% and 61.6% respectively. This was in-line with other study [18] but it was lower than other study [10]. Reasons for these differences may be due to the cultural characteristics of the respondents, study methodology and set up of services.…”
Section: Discussionsupporting
confidence: 89%
“…The 22 included studies reported on factors influencing and barriers to KMC utilisation amongst PLBWIs mostly published between 2012 and August 2020. The included studies comprised four cross-section studies 36 , 37 , 38 , 39 three randomised control trial studies, 40 , 41 , 42 one explorative study 43 seven descriptive studies, 44 , 45 , 46 , 47 , 48 , 49 , 50 one longitudinal study, 49 one qualitative study, 51 two dissertations 39 , 52 and two formative study. 47 , 53 Almost 10 studies were based on face-to-face interviews, 36 , 37 , 38 , 43 , 44 , 45 , 46 , 47 , 48 , 50 of which seven were qualitative study interviews, 36 , 37 , 43 , 47 , 48 , 50 , 53 three were mixed-method studies 38 , 44 , 46 and nine were quantitative studies.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies comprised four cross-section studies 36 , 37 , 38 , 39 three randomised control trial studies, 40 , 41 , 42 one explorative study 43 seven descriptive studies, 44 , 45 , 46 , 47 , 48 , 49 , 50 one longitudinal study, 49 one qualitative study, 51 two dissertations 39 , 52 and two formative study. 47 , 53 Almost 10 studies were based on face-to-face interviews, 36 , 37 , 38 , 43 , 44 , 45 , 46 , 47 , 48 , 50 of which seven were qualitative study interviews, 36 , 37 , 43 , 47 , 48 , 50 , 53 three were mixed-method studies 38 , 44 , 46 and nine were quantitative studies. Out of the 22 studies, 19 were conducted in the facility 36 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 54 , 55 , 56 and three were c...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation